Semiotic Analysis of The Garuda Pancasila on The Indonesian National Football Team Jersey - Wicaksana, Adhika; Saidi, Acep Iwan (Jurnal Lemhannas RI, 2024)
Purpose: Garuda Pancasila, displayed on the Indonesian National Team's jersey, has been a prominent feature in football since Indonesia's independence. It is widely embraced by players, fans, and the Indonesian community, symbolising national resilience. Study Design/Methodology/Approach: This descriptive qualitative study aims to elucidate the significance of the Garuda Pancasila emblem on the Indonesian national football team's jersey. The research employs Roland Barthes' semiotic method and Althusser's ideological theory, focusing on jerseys from the 2022–2024 seasons. Textual analysis is utilised to interpret the data. Findings: The study reveals that the Garuda Pancasila emblem transcends mere decoration; it is a revered symbol embedded in the national identity and pride of its wearers. Since the Old Order under President Soekarno, the emblem has been a vehicle for political expression and ideological discourse within Indonesian society. Originality/Value: The findings underscore the enduring importance of the Garuda Pancasila emblem, which continues to embody national unity, resilience, and ideological continuity in modern Indonesia. Its presence on the jersey reflects a rich cultural heritage and political history, highlighting the emblem's significance in both national and sports contexts.